2021
DOI: 10.1186/s12884-021-03593-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nicotine and maternal BMI on fetal birth weight

Abstract: Background According to the World Health Organization, smoking is the most important risk factor for adverse pregnancy outcomes in industrialized nations. As the individual factors (body mass index – BMI (kg/m2) – and cigarette consumption) have been extensively investigated in pregnancy, we aimed to establish how maternal BMI and nicotine interact with regard to perinatal outcomes and birth weight. Methods Data from 110.047 singleton pregnancies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
3
11
2
Order By: Relevance
“…Likewise, Wang et al, who also carried out the determination of the lipids in the 24th and 36th week of pregnancy, we were able to show that the HDL concentration of the mothers is inversely correlated with the birth weight of the newborns [21], whereby we were able to show that the HDL concentration also seems to in uence growth and weight in the longer term up to the rst year of life. The in uence of maternal BMI on birth weight [24] and the correlation to SES [25] has already been shown in other studies. However, no study could be found that examined the in uence of maternal BMI or serum lipid levels on anthropometric markers other than birth height or weight, as shown here.…”
Section: Discussionsupporting
confidence: 70%
“…Likewise, Wang et al, who also carried out the determination of the lipids in the 24th and 36th week of pregnancy, we were able to show that the HDL concentration of the mothers is inversely correlated with the birth weight of the newborns [21], whereby we were able to show that the HDL concentration also seems to in uence growth and weight in the longer term up to the rst year of life. The in uence of maternal BMI on birth weight [24] and the correlation to SES [25] has already been shown in other studies. However, no study could be found that examined the in uence of maternal BMI or serum lipid levels on anthropometric markers other than birth height or weight, as shown here.…”
Section: Discussionsupporting
confidence: 70%
“…Of note, maintaining desirable lifestyle habits should not be limited to the period of gestation, since numerous evidence suggests that preconception health could be even more important for ensuring favorable pregnancy course and outcome [ 41 ]. Interestingly, we did not detect any significant differences in newborns’ weight with respect to maternal smoking habits, although a firm relationship between smoking before and during pregnancy and adverse pregnancy outcomes was established by many previous studies [ 42 , 43 ]. Such atypical results could arise due to a small sample size in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…Thus, these meta‐analyses suggest modest associations of maternal preconception/prenatal tobacco use with both poorer social communication skills and elevated risk for ASD. These findings add to the numerous other adverse outcomes associated with maternal smoking during gestation: higher risks for ectopic pregnancy (Gaskins et al, 2018 ; Handler et al, 1989 ; Stergachis et al, 1991 ), fetal loss (Flenady et al, 2011 ; Marufu et al, 2015 ; Pineles et al, 2014 ; Pineles et al, 2016 ), preterm delivery (Liu et al, 2020 ; Soneji & Beltrán‐Sánchez, 2019 ), and lower birthweight (Blatt et al, 2015 ; Günther et al, 2021 ; Pereira et al, 2017 ; Tayie & Powell, 2012 ), as well as childhood outcomes of asthma (Harju et al, 2016 ; McEvoy & Spindel, 2017 ; Neuman et al, 2012 ) and attention deficit‐hyperactivity disorder (Huang et al, 2018 ; Langley et al, 2005 ; Sourander et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%